FAKTOR RISIKO PENYAKIT KANKER PAYUDARA DI WILAYAH ASIA (DENGAN PENDEKATAN STUDI META ANALISIS) - Alfita Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Breast cancer is the most common cancer in women. With an estimated 1.7 million cases and 521,900 deaths in 2012. Of these estimates, 39% in Asia, 29% in Europe, 15% in America, 8% in Africa, and 1.1% in Australia.This study aims to see risk factors for breast cancer incidence in the Asian region. This research is quantitative with the design of meta-analysis study of the research with the design of case-control and cohort studies. Search through ProQuest, PubMed, Biomed Central, and EBSCO Host databases. The data is processed using RevMan 5.3 application. The results showed a significant correlation to family history of cancer (OR: 1.57 95%CI 1.22-2.02), age of menopause ≥50 years (OR: 1.20 95%CI 1.04-1,39), and the first delivery age was ≥30 years (OR: 1.54 95%CI 1.18-2.02) with breast cancer in the Asian Region. While age (OR: 1,11 95%CI 1.00-1.24), age at menarche